Význam urokinázy a jejích inhibitorů pro invazi a metastazování zhoubných nádorů - Halámková, J; Kiss, I; Tomášek, J; Pavlovský, Z; Tuček, S; Penka, M (Vnitrni lekarstvi, 2012)
Fibrinolysis is process, which leads to the degradation of fibrin to fibrin monomers. Fibrinolysis helps to regulate hemostasis and prevents the creation of inappropriately large thrombus, which could reduce blood flow to the bloodstream. The main enzyme involved in fibrinolysis is plasmin. Tissue plasminogen activator (tPA) and urokinase (uPA) are agents converting plasminogen into active plasmin, together with urokinase receptor (uPAR) and urokinase inhibitors (PAI 1, PAI 2, PAI 3 and protease nexin) form plasminogen activator system (PAS) which is among others also part of the metastatic cascade and significantly contributes to invasive growth and angiogenesis of malignant tumours. In contrast to tPA that is fundamental in fibrinolysis, uPA plays an essential role in tissue degradation as part of physiological and pathological processes. uPAR is a GPI (glycosylphosphatidylinositol)-anchored protein. The binding of uPA to uPAR results in activation of protein tyrosine kinase, protein kinase C and MAP kinase. At the same time, direct signalling pathway via Jak/STAT cascade utilising signalling transduction of Scr-like protein tyrosine kinase have also been described. uPAR expression is regulated by many growth factors, e.g. EGF, FGF-2 and HGF. It seems that individual PAS factors are involved in the process of rendering malignant tumors invasive. To what degree this influence is essential to specific malignancies, should be answered by further research. In the article the authors present a summary of findings about the interaction of fibrinolysis and tumor process, especially on the effects of urokinase and other activators and their inhibitors in metastasis of malignant tumors. The text contains information on the factors theirs introduction into practice is still the subject of numerous discussions, but in the future, individual PAS factors could play an important role in planning treatment strategies and also could become targets of targeted therapy.
Keywords: invazivní růst nádoru; aktivátory plazminogenu; Plasminogen Activators; Tissue Plasminogen Activator; lidé; Neoplasm Invasiveness; aktivátor plazminogenu urokinázového typu; Humans; Urokinase-Type Plasminogen Activator; Neoplasm Metastasis; metastázy nádorů; tkáňový aktivátor plazminogenu